2022
DOI: 10.1029/2022jc019218
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Open‐Ocean Forcing and Local Wind to Sea Level Variability Along the West Coasts of Ocean Basins

Abstract: This study aims to reconstruct sea level at the coast by quantifying relative contributions of local wind forcing and the penetrated open‐ocean signals, and thus to build a dynamical connection that seamlessly links the ocean basin to the coast. A linear, modified arrested topographic wave (ATW) model is used to examine the transmission of interior sea level across the continental shelf and the role of alongshore wind in determining the coastal sea level. The local wind stress substantially influences the coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…(2019) demonstrated that the Atlantic Meridional Overturning Circulation (AMOC) and US east coast DSL shared a common driver in the large scale atmospheric variability that could result in erroneously concluding that the AMOC drove coastal DSL variability when in fact local winds and atmospheric pressure were the causal drivers. The relative importance and mechanisms involved in deep ocean effects on coastal DSL have been studied in a number of publications in relation to the western boundary of the North Atlantic (e.g., Hong et al., 2000; Lin et al., 2022; Piecuch et al., 2019; Wang et al., 2022; Wise, Polton, et al., 2020; Woodworth et al., 2014, and others). Far less attention has been directed at eastern boundaries, however.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) demonstrated that the Atlantic Meridional Overturning Circulation (AMOC) and US east coast DSL shared a common driver in the large scale atmospheric variability that could result in erroneously concluding that the AMOC drove coastal DSL variability when in fact local winds and atmospheric pressure were the causal drivers. The relative importance and mechanisms involved in deep ocean effects on coastal DSL have been studied in a number of publications in relation to the western boundary of the North Atlantic (e.g., Hong et al., 2000; Lin et al., 2022; Piecuch et al., 2019; Wang et al., 2022; Wise, Polton, et al., 2020; Woodworth et al., 2014, and others). Far less attention has been directed at eastern boundaries, however.…”
Section: Introductionmentioning
confidence: 99%